Temperature and Fertility: Evidence from Spanish Register Data - Risto Conte Keivabu; Marco Cozzani; Joshua Wilde (Institute of Labor Economics (IZA), 2023)
In this paper, we combine administrative data for continental Spain from 2010 to 2018 with meteorological data to identify the effect of temperature on fertility. We demonstrate that warm (25-30°C) and hot days (>30°C) decrease total fertility rate (TFR) in Spain, and that the estimated decrease is higher than the effects estimated in previous literature for other countries. Moreover, we show that locations with a colder climate are more vulnerable to the impact of heat. Our results suggest that the global impact of climate change on population dynamics may be understated, especially without adaptation and mitigation measures, and that temperature increases may exacerbate the socio-economic consequences of low fertility such as population ageing.
Keywords: J13; J11; J18; I12; Q54; Q56; 330; fertility; TFR; temperature; heat; Spain